REPRESENTASI MAKNA IKHLAS DALAM FILM ANIMASI NUSSA EPISODE BELAJAR IKHLAS - Syafira Hidayat, Fakhrur Rozi, Ahmed Fernanda Desky (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2022)
Abstract: This study will discuss how the representation of sincere’s meaning was shown in the animation film named Nussa. Representation in a film is a depicition of something that is poured through the story in a film. “Nussa ad Rarra” is an Indonesian animated film produced by The Little Giantz which is shown on the official Youtube platform Nussa Official Chanel. This film comes against the background of the decline in the character of the nation’s children. Instilling a sincere attitude, especially to children, requires extra patience, because children’s souls are easily influenced by things that can damage their righteous intetions. This episode of “Learning of Sincere” illustrates how Nussa teaches her sister Rarra to always act sincerely. Nussa, who is a person with a disability, told how she accepted her situationn which had been decreed by Allah SWT. This tudy aims to describe the sincere representation contained in the Nussa animation by analyzing the sign in each scene based on the meaning of conotation, denotation, and myth. Using a qualitative descriptive approach and Roland Barthes’ semiotic analysis, it was found that the sincere meaning contained in Nussa’s animation is not to feel disappointed if the good deeds we have done didn’t get an appreciation, accept God’s decree with pleasure, and do not expect anything in return in everythig. Keywords: Representation, Sincere’s Meaning, Animated Film